Pentecostalism and politics of conversion in India - Sahoo, Sarbeswar (Cambridge Cambridge University Press, 2018)
This book studies the politics of Pentecostal conversion and anti-Christian violence in India. It asks: why has India been experiencing increasing incidents of anti-Christian violence since the 1990s? Why are the Bhil Adivasis increasingly converting to Pentecostalism? And, what are the implications of conversion for religion within indigenous communities on the one hand and broader issues of secularism, religious freedom and democratic rights on the other? Drawing on extended ethnographic fieldwork amongst the Bhils of Northern India since 2006, this book asserts that ideological incompatibility and antagonism between Christian missionaries and Hindu nationalists provide only a partial explanation for anti-Christian violence in India. It unravels the complex interactions between different actors/ agents in the production of anti-Christian violence and provides detailed ethnographic narratives on Pentecostal conversion, Hindu nationalist politics and anti-Christian violence in the largest state of India that has hitherto been dominated by upper caste Rajput Hindu(tva) ideology.
Includes bibliographical references (pages 165-200) and index.
Keywords: Pentecostalism; Conversion; Pentecostals; Christians